PENERAPAN ASSOCIATION RULE PADA DATA PERSEDIAAN BAHAN BAKU DI PRO AB CHICKEN JAMBI: APRIORI ALGORITHMS, ASSOCIATION RULES, DATA MINING, SALES TRANSACTION - Wahyuning Astuti, Reny; Simorangkir, Lucy; Wijaya, Hendra (FORTECH (Journal of Information Technology), 2017)
Data Mining is technique extract useful and valuable information from very large database. The frequent occurrence of a void of raw material inventory for menus often purchased simultaneously by customers is the result of the lack of information about customer spending habits. So it is necessary to extract the information on the transaction data with association rules techniques to know the menu often purchased simultaneously by the customer. Association rules are also often called Market Basket Analysis (MBA), the algorithm used in association rules in this research is an a priori algorithm with sales menu transaction dataset. The results obtained from data processing sales transaction is combination of itemset Association support and confidence value. The information generated is by knowing the most widely sold products then the company can develop strategies by adding raw material inventory.